Aferition of the arterial pressure: assistant’s theoretical and practical knowledge and nursing technicians - Francisca Elisângela Teixeira Lima; Thelma Leite de Araújo; Thereza Maria Magalhães Moreira (Rev Rene)
The nursing team is responsible for most of the aferições of arterial pressure (PA), and incorrect measures of the PA can take to serious consequences. Readings falsely high they do with that the patient has to be submitted to treatment and erroneously low, they deprive it of the same. It is objectified to identify the assistants’ theoretical and practical knowledge of nursing technicians of a public hospital on the steps of the correct technique of the measure of the arterial pressure, relating it with the procedure recommended by American Heart Association. The study was of the descriptive exploratory type. The population was constituted by assistants and nursing technicians that work in this hospital, being the auxiliary simple aleatorited sample composed of 31 and 19 technicians. It was used two instruments: a questionnaire with open and shut questions and an another of observation (check-list). As results obtained to the they refer the steps of the procedure of the verification of the PA, it prevailed them accomplished all day in the practice, such as: to locate the brachial artery; to place the manguity in the appropriate place; the heard stethoscope us; the diaphragm on the brachial artery and to close the valve of the cuff. It is ended that the appraised theoretical-practical knowledge was shown incomplete and, until, incorrect, being the faultier theoretical knowledge in relation to the practical.